Grub dbaṅ Rig ʼdzin rgyal poʼi phyi naṅ gsaṅ ba ṅes don gyi rnam thar źal gdams bkaʼ ʼbum : the life and songs of spiritual insight of Grub-dbaṅ Rig-ʼdzin-rgyal-po - Rig-ʼdzin-rgyal-po, b. 1692 (Sanje Dorje, 1977)
Autobiographical writings of a teacher of the Nyingmapa and Drikung Kargyudpa traditions from Kongpo in southeastern Tibet.